Enclosure, writing, and resistance: revisiting the prose of Daniil Kharms. Issue 1 (3rd April 2017) - Brookes, Alec
ABSTRACT: The author argues that discipline – operating through the distribution of individuals by means of enclosure and surveillance – is crucial to understanding Daniil Kharms's prose of the 1930s. The author focuses on three of his mini-stories, first looking at mechanisms of surveillance in "Dream, " examining their effects upon the psyche that have material impacts on the body of the individual. Then he turns to a trajectory of enclosure that operates from the urban commons ("Trial by Lynching") to the home ("An Unexpected Drinking Party"). The centripetal trajectory of enclosure ends in all cases at the body as the endpoint of discipline and, ultimately, the site of Kharms's "grotesque resistance, " challenging the enclosure of the body from the point of its confinement. He also looks to how paper – as theme in and medium of Kharms's work – operates within these spatial dynamics. He draws upon Harold Innis, who associated the rise of print in the United States with the "space bias" of communication. Reading Foucault and Innis together, Kharms's short prose works can be understood as a contestation of the space bias of print media in the Stalinist era, prompting Kharms's retreat to the contours of the body as a site of struggle.